Characterization of Welded Joints - Silva, Francisco J. G. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Welding remains one of the most studied manufacturing processes worldwide. It has always assumed a vital importance in terms of research, and the market demand for increasingly complex solutions has kept the search for new solutions around welding more and more alive. This book describes, in 14 chapters, recent investigations around various welding processes, showing new developments in important areas, such as biomedicine or the automotive industry. Following the current trend, several developments around the friction stir welding process are also described. However, other processes are also studied, and new interesting developments are presented. Problems normally felt in welding, such as the installation of internal stresses or the generation of defects are also studied, and very interesting solutions are provided. Thus, this book is of particular importance for a very wide audience, ranging from the technician who is curious to want to know more and more, to the professor who seeks the latest developments in the matter to prepare his classes.